The impact of regular activity and exercise intensity on the acute effects of resistance exercise on cognitive function - Engeroff, T.; Banzer, W.; Niederer, D. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Beneficial acute effects of resistance exercise on cognitive functions may be modified by exercise intensity or by habitual physical activity. Twenty-six participants (9 female and 17 male; 25.5 ± 3.4 years) completed four resistance exercise interventions in a randomized order on separate days (=48 h washout). The intensities were set at 60%, 75%, and 90% of the one repetition maximum (1RM). Three interventions had matched workloads (equal resistance*nrepetitions). One intervention applied 75% of the 1RM and a 50% reduced workload (resistance*nrepetitions = 50%). Cognitive attention (Trail Making Test A—TMTA), task switching (Trail Making Test B—TMTB), and working memory (Digit Reading Spans Backward) were assessed before and immediately after exercise. Habitual activity was assessed as MET hours per week using the International Physical Activity Questionnaire. TMTB time to completion was significantly shorter after exercise with an intensity of 60% 1RM and 75% 1RM and 100% workload. Friedman test indicated a significant effect of exercise intensity in favor of 60% 1RM. TMTA performance was significantly shorter after exercise with an intensity of 60% 1RM, 90% 1RM, and 75% 1RM (50% workload). Habitual activity with vigorous intensity correlated positively with the baseline TMTB and Digit Span Forward performance but not with pre- to post-intervention changes. Task switching, based on working memory, mental flexibility, and inhibition, was beneficially influenced by acute exercise with moderate intensity whereas attention performance was increased after exercise with moderate and vigorous intensity. The effect of regular activity had no impact on acute exercise effects.